Experimental evaluation of the impact of mobility management protocols on HTTP adaptive streaming. Issue 6 (1st November 2017) - Sani, Yusuf; Isah, Musab; Edwards, Christopher; Mauthe, Andreas
Abstract : Video content is increasingly being consumed on the move using mobile devices such as smart phones and tablets. In order to deal with the challenges of heterogeneity of network access technologies and fluctuating resources, which are inherent features of mobile communication, HTTP adaptive streaming (HAS) is becoming the default technology for online video streaming. However, little research has been carried out to better understand the impact of handover schemes of the various mobility management protocols on the video quality of HAS. In this study, the authors present a comprehensive experimental measurement of the impact of handover on three representative HAS players. First, they implement three existing mobility management protocols, MIPv6, LISP‐MN and PMIPv6, on a network testbed. Using the fluid flow mobility model, the impact of frequent handover on the average video quality, the bandwidth utilisation and stability of the players was investigated. Their results show a degradation of all the observed parameters in all the reviewed players.